Social determinants of psychological distress in a nationally-representative sample of South African adults() - Myer, Landon (2008)
There is substantial evidence from developed countries that lower socioeconomic status (SES) is associated with increased occurrence of mental illness, and growing interest in the role of social support and social capital in mental health. However, there are few data on social determinants of mental health from low- and middle-income nations. We examined the association between psychological distress and SES, social support and bonding social capital in a nationally-representative sample of South African adults. As part of a national survey of mental health, a probability sample of 4351 individuals was interviewed between 2002 and 2004. Non-specific psychological distress was measured using the Kessler K-10 scale. SES was assessed from an aggregate of household income, individual educational and employment status, and household material and financial resources. Social support, bonding social capital and traumatic life events were measured using multi-item scales. The mean age in the sample was 37 years and 76% of participants were black African. Measures of SES and social capital were inversely associated (p < 0.001). Both recent and traumatic life events were more common among individuals with low levels of SES and social support. After adjusting for participant demographic characteristics and life events, high levels of psychological distress were most common among individuals with lower levels of SES and social capital. There was no independent association between levels of social support and psychological distress. The occurrence of recent life events appeared to partially mediate the association between SES and psychological distress (p = 0.035) but not the association involving social capital (p = 0.40). These data demonstrate persistent associations between levels of SES, social capital and psychological distress in South Africa. The increased frequency of recent life events appears to only partially explain higher levels of psychological distress among individuals of lower SES. Additional research is required to understand the temporality of this association as well as mechanisms through which SES and social capital influence mental health in low- and middle-income settings where high levels of poverty and trauma may contribute to excess burden of mental illness.